Pengaruh Persepsi Harga Dan Kualitas Produk Terhadap Keputusan Pembelian: (Survei Pada Konsumen Heler CV Wirabuana Tasikmalaya) - Shahnaz Tsamrotul Paudah; Kusuma Agdhi Rahwana; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study was to determine and analyze the effect of price perception and product quality variables on purchasing decisions on consumers of Heler CV Wirabuana Tasikmalaya. The research method used is a survey method with data obtained directly through a questionnaire to 100 respondents taken from the consumer heler CV Wirabuana. The technique used is multiple regression. Based on the results of this study, it is known that there is a simultaneous significant effect between Price Perception and Product Quality on Purchase Decisions. Price perception partially has no significant effect on Purchase Decisions and Product Quality Partially has a significant effect on Consumer Purchase Decisions Heler CV Wirabuana Tasikmalaya.